Bee Keeping; An Alternative Source of Income Generation - R, Umaru; W, Ronald A. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
This study underscores Bee Keeping as an Alternative Source of Income Generation which involves construction of beehive and apiculture management practices. The result of this work covers the period of four (4) years. The results showed that the price of honey increases every year (2021; #2000, 2022; #2500, 2023; #3000 and 2024; # 4500 per litre. For the four years covered, a total of 219 litres were harvested and sold for the sum of #593,500. Beekeeping has many advantages aside financial or economic gains. Bees pollinate numerous species of plants, thus contributing immensely to agricultural production, cross breeding and the conservation of biological diversity. It generates income for the beekeepers. Apiculture requires little resources to set-up using local materials. It is less demanding, therefore, neither competes for time or other agricultural enterprises for land or space. It is not labour intensive and easy to keep. Apiculture is lucrative business and can be an alternative source of income for civil servants and others. It is a suitable enterprise for poverty reduction. It is compactable for all sexes, age and social status. The results of this work recommends that, both the government and non-governmental organisations need to embark on massive awareness campaigns toward bringing the improved methods to the poor majority of Nigerians, and appropriate policymaking to encourage and protect the apiculture business as this is a relatively new field in Nigeria.